2013
DOI: 10.1590/s1677-32252013000200015
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a desensitizing dentifrice on the bond strength of different adhesive systems

Abstract: Aim: This in vitro study evaluated the effect of using a dental hypersensitivity treatment on the bond strength to dentin of etch-and-rinse and self-etching simplified adhesive systems. Methods: 40 healthy molars were used. The crowns of teeth were removed at the dentinoenamel junction, and remaining roots were sectioned in the mesiodistal direction along their long axis, separating the buccal and lingual/palatal halves. The segments obtained were ground, keeping the buccal or lingual/palatal face turned downw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
0
4
1
Order By: Relevance
“…However, our results differ from Cavalcanti et al (2013), which observed a significant reduction in bond strength to dentin after the use of a desensitizing dentifrice Colgate Sensitive Pro-Relief, when associated to a one-step, self-etching, bonding system. Although those bonding agents showed higher acidity compared to the one used in the present study (twostep, self-etching) (Van Meerbeek et al), which could make dentin hybridization less sensitive to the previous application of desensitizing agents, other aspects must be considered when referring to one-step, self-etching, systems: the inhibition of polymerization by the acidity of this type of adhesive system, the adhesive layer thickness, phase separation between hydrophilic and hydrophobic components, and greater sensitivity to hydrolysis (Van Meerbeek et al).…”
Section: Discussioncontrasting
confidence: 99%
“…However, our results differ from Cavalcanti et al (2013), which observed a significant reduction in bond strength to dentin after the use of a desensitizing dentifrice Colgate Sensitive Pro-Relief, when associated to a one-step, self-etching, bonding system. Although those bonding agents showed higher acidity compared to the one used in the present study (twostep, self-etching) (Van Meerbeek et al), which could make dentin hybridization less sensitive to the previous application of desensitizing agents, other aspects must be considered when referring to one-step, self-etching, systems: the inhibition of polymerization by the acidity of this type of adhesive system, the adhesive layer thickness, phase separation between hydrophilic and hydrophobic components, and greater sensitivity to hydrolysis (Van Meerbeek et al).…”
Section: Discussioncontrasting
confidence: 99%
“…Many factors can influence the bonding performance of adhesive systems to dentin, among these are: dentin substrate 13 , dentin treatment 14 and chemical composition of the adhesive systems, including the solvents. Bond 1 SF is a light-cured, one-coat self-etch adhesive system in which the manufacturer has removed the solvent that is contained in virtually all other adhesive systems.…”
Section: Discussionmentioning
confidence: 99%
“…solvent free adhesive system (Bond 1 SF) exhibited the statistically significant lowest bond strength (11.3±1.54 MPa) when compared with the other two adhesive systems, Braz J Oral Sci 13…”
mentioning
confidence: 93%
“…Adhesion values similar to those of non-treated dentin were generated after such treatment. [9,10] Ariffin et al studied the release of fluoride by glass ionomer cement after coating with silver fluoride. They concluded that the application of a layer of 10% silver fluoride improves the concentration of fluoride released from this material.…”
Section: Discussionmentioning
confidence: 99%